The dark side of multiunit discounts: Multiunit discounts reduce rest of basket revenue. (May 2023) - Bhatt, Siddharth; Pai, Dinesh R.; DelVecchio, Devon
Abstract: Multiunit discounts refer to the practice of offering a discount on purchase of multiple units of a product. An example of multiunit discounts, which are commonly used by retailers, is '3 for $10'. While past research suggests that multiunit discounts generate higher sales than per-unit discounts, there is no research on how such discounts affect sales of other products in the store. We argue that consumers exposed to multiunit discounts may purchase the products offered as such to benefit from the deal. These customers, however, will spend less on other products, resulting in lower revenue from the rest of the basket during the shopping trip. Based on theoretical insights, we propose why such an effect could occur and test our arguments using store data and a lab experiment. The findings of this research suggest that multiunit discounts have a multifaceted impact on consumer decision-making. We also discuss the theoretical, managerial, and methodological contributions of this research.